Secrets stolen, fortunes lost preventing intellectual property theft and economic espionage in the 21st century - Burgess, Christopher; Power, Richard (Rockland, Mass. : Syngress ; Oxford : Elsevier Science [distributor], 2008)
The threats of economic espionage and intellectual property (IP) theft are global, stealthy, insidious, and increasingly common. According to the U.S. Commerce Department, IP theft is estimated to top $250 billion annually and also costs the United States approximately 750,000 jobs. The International Chamber of Commerce puts the global fiscal loss at more than $600 billion a year. Secrets Stolen, Fortunes Lost offers both a fascinating journey into the underside of the Information Age, geopolitics, and global economy, shedding new light on corporate hacking, industrial espionage, counterfeiting and piracy, organized crime and related problems, and a comprehensive guide to developing a world-class defense against these threats. You will learn what you need to know about this dynamic global phenomenon (how it happens, what it costs, how to build an effective program to mitigate risk and how corporate culture determines your success), as well as how to deliver the message to the boardroom and the workforce as a whole. This book serves as an invaluable reservoir of ideas and energy to draw on as you develop a winning security strategy to overcome this formidable challenge. Its Not Someone Elses Problem: Your Enterprise is at Risk Identify the dangers associated with intellectual property theft and economic espionage The Threat Comes from Many Sources Describes the types of attackers, threat vectors, and modes of attack The Threat is Real Explore case studies of real-world incidents in stark relief How to Defend Your Enterprise Identify all aspects of a comprehensive program to tackle such threats and risks How to Deliver the Message: Awareness and Education Adaptable content (awareness and education materials, policy language, briefing material, presentations, and assessment tools) that you can incorporate into your security program now.
Your Enterprise At Risk; The Tale of the Targeted Trojan; When Insiders and/or Competitors Target Business; Intellectual Property; When State Entities Target Business? Intellectual Property; When Piracy, Counterfeiting and Organized Crime Target Business; Intellectual Property; Virtual Roundtable on Intellectual Property and Economic Espionage; Elements of a Holistic Program; Case Study: Cisco's Award-Winning Awareness Program; Case Study of A Bold, New Approach in Awareness and Education Meets An Ignoble Fate; Case Study--The Mysterious Social Engineering Attacks on Entity X; Personnel Security; Physical Security-The "Duh" Factor; Information Security; The Intelligent Approach; Protecting Intellectual Property in Crisis Situation; How to Sell Your Intellectual Property Protection Program; Appendices.
Includes bibliographical references and index.
Keywords: Business intelligence; Intellectual property -- Economic aspects; Intellectual capital -- management; Business intelligence. Intellectual property -- Economic aspects. Intellectual capital -- Management; Electronic books